The great Gatsby - Luhrmann, Baz; Pearce, Craig (Screenwriter); DiCaprio, Leonardo; Maguire, Tobey, 1975-; Mulligan, Carey, 1985-; Edgerton, Joel, 1974-; Fisher, Isla, 1976-; Clarke, Jason, 1969-; Armstrong, Craig, 1959-; Fitzgerald, F. Scott (Francis Scott), 1896-1940.; Bazmark (Firm); Warner Bros.; et al. (Burbank, CA : Distributed by Warner Home Video, 2013)
The Great Gatsby follows viable writer Nick Carraway as he leaves the Midwest and comes to New York City in the spring of 1922. Chasing his own American dream, Nick lands next door to Jay Gatsby, and across the bay from his cousin, Daisy, and her husband, Tom Buchanan. Nick is drawn into the captivating world of the rich and their loves and deceits. As he bears witness, he pens a tale of impossible love, incorruptible dreams, and tragedy, and holds a mirror to our own modern times and struggles.
disc 1. Feature film -- disc 2. Bonus disc.
DVD; NTSC, region 1; widescreen presentation in "Letterbox" format enhanced for widescreen TVs; dual-layer.
Closed-captioned; English, dubbed French or dubbed Spanish (Dolby digital 5.1 surround) dialogue, with optional subtitles in Spanish or French and English subtitles for the deaf and hard of hearing (SDH).
Leonardo Dicaprio, Tobey Maguire, Carey Mulligan, Joel Edgerton, Isla Fisher, Jason Clarke.
Music, Craig Armstrong ; editors, Matt Villa, Jason Ballantine, Jonathan Remond ; director of photography, Simon Duggan.
Based on the novel by F. Scott Fitzgerald.
Originally produced as a motion picture in 2013.
Keywords: Upper class -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama; Millionaires -- New York (State) -- New York -- Drama; Fitzgerald, F. Scott -- 1896-1940 -- Film adaptations; Long Island (N.Y.) -- Drama; Romance films; Film adaptations; Fiction films; Feature films; Video recordings for the hearing impaired; Feature films -- Australia; Feature films -- United States